2011
DOI: 10.1007/s10722-011-9687-4
|View full text |Cite
|
Sign up to set email alerts
|

Spanish melons (Cucumis melo L.) of the Madrid provenance: a unique germplasm reservoir

Abstract: Melon (Cucumis melo L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…A loss of attributes from the traditional varieties to their commercial homologues is considerably evident (banana-mango-peach aromas, acidity, Wbrosity and orange fresh). The Piel de Sapo market class showed more sensorial homogeneity, as found in other studies [8,25,33]. Most sensorial attributes of the commercial varieties 'Piñonet Pinet' and 'Piel de Sapo Ricamiel' have weakened in the breeding process.…”
Section: Detection Of Relevant Sensorial Diverences Between Homologousupporting
confidence: 74%
See 1 more Smart Citation
“…A loss of attributes from the traditional varieties to their commercial homologues is considerably evident (banana-mango-peach aromas, acidity, Wbrosity and orange fresh). The Piel de Sapo market class showed more sensorial homogeneity, as found in other studies [8,25,33]. Most sensorial attributes of the commercial varieties 'Piñonet Pinet' and 'Piel de Sapo Ricamiel' have weakened in the breeding process.…”
Section: Detection Of Relevant Sensorial Diverences Between Homologousupporting
confidence: 74%
“…However, until now, no author has used a characterization protocol to obtain a sensory proWle of a set of traditional melon varieties. Some studies have demonstrated the extraordinary agro-morphological and molecular variability of these varieties, using a multidisciplinary approach [25,33]. The goal of present study is to analyze melon diversity through sensory analysis, applying the previously published protocol [8].…”
Section: Introductionmentioning
confidence: 99%
“…The average alleles per locus in Spanish melons ranged from 1.05 to 2.82 (Escribano et al. ) and 2.47 in Greek and Cypriot melons (Emmanouil et al. ), compared to 4.44 for Indian melon accessions in the current study.…”
Section: Discussionmentioning
confidence: 45%
“…Fergany et al (2011) also reported a PIC value of 0.544 in a set of Indian melon accessions, which is in the range Fig 1: Two different methods for determining optimal value of K: (a) the ad hoc procedure described by Pritchard et al (2000) where the K value is increasing (b) the second-order statistic (DK) developed by Evanno et al (2005), the sharp peak of DK at K = 4 suggesting four sub populations of results obtained in the current experiment. The average alleles per locus in Spanish melons ranged from 1.05 to 2.82 (Escribano et al 2012) and 2.47 in Greek and Cypriot melons (Emmanouil et al 2009), compared to 4.44 for Indian melon accessions in the current study. Although it would not be appropriate to compare results across these experiments as the number of accessions and markers employed would influence the allele number, the current findings provide a suggestive evidence of a high variability among Indian melon germplasm.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation